Proposta e avaliação de um sistema assistivo para auxílio da pessoa com deficiência visual na seleção de produtos - SILVA, Andrei Luiz Demetrio e (Universidade Federal do Pará, 2020)
The act of making purchases is seen as a simple task for most people. However, for someone with visual impairment it can mean something complex or even impossible to realize without the help of others. In order to overcome this barrier and enable the realization of the selection of products in an autonomous way by the visually impaired, the proposed system was developed. Using a microcontroller interconnected to a radio frequency sensor and an audio reproducer, an embedded system (coupled to a glove) was built, which together with a database query service made possible its implantation. Its use was evaluated by two groups of participants through the accomplishment of a case study set in a supermarket. The first group consisted only of visually impaired, while the second group was blind sighted participants, who were blindfolded to simulate newly acquired blindness. With the accomplishment of this work, it was possible for people with visual impairment to perform a product selection process autonomously, reaching a mean assertiveness index of 92.5%.